'At the level of the word: Nurturing justice in therapeutic conversations'. Issue 2 (3rd April 2019) - Paré, David
ABSTRACT: The issue of social justice and how it unfolds in the lives of persons seeking counselling has been steadily gaining attention in recent times. This development marks a departure from an individualistic perspective that construes problems as functions of personal deficits, thereby overlooking the many social inequities that contribute to the challenges people face. The turn towards social justice manifests primarily in a call for advocacy on behalf of therapy clients. While celebrating these developments, this article suggests that it is not just in interactions outside the consulting room that injustices may be perpetrated. The author invites attention to the ways in which social justice, or the lack thereof, can be understood to unfold within counselling conversations.